Opportunities of frugality in the post-Corona era - Cornelius Herstatt; Rajnish Tiwari (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2020)
Objective of this discussion paper is twofold: First, we assess the likely impact of the Corona crisis on the economic and societal choices of people, especially in relation to voluntary simplicity. Second, we contextualize the impact of those choices in the field of innovation management. Taking a normative-conceptual perspective we seek to understand in how far frugality, and inter alia, frugal innovations can play a role in better managing the after-effects of the Corona crisis and what implications arise out of this for the relevant societal stakeholders, especially for corporates, policy makers and consumers. Taking note of historical discussions of the role of frugality as a "virtuell", we propose that the currently ongoing fourth renaissance of frugality needs to - and is likely to - emerge as a megatrend that may shape a frugal "AGE" resulting in "affordable green excellence" as the dominant innovation paradigm. To realize this potential, however, it is necessary to move away from the unidimensional focus on monetary affordability of frugal solutions. There is a need for developing a more comprehensive and multidimensional understanding of affordability that is targeted at ensuring financial, societal, infrastructural and ecological affordability of frugal products, services, technologies and business models. Frugal innovators and entrepreneurs should not merely target "significant cost reduction" in relation to existing substitute products but rather aim at ensuring "high affordability" that will open up new business arenas with means of breakthrough innovations and technological excellence. This paradigm shift requires action from all relevant stakeholders including policymakers.
Keywords: 330; Corona Crisis; Covid-19 Pandemic; Frugality 4.0; Frugal Innovation; Affordable Green Excellence; Circular Economy; Voluntary Simplicity